Independent directors' board networks and controlling shareholders' tunneling behavior - Yunsen Chen; Yutao Wang; Le Lin (China Journal of Accounting Research, 2014)
As one of the channels by which board directors build important relationships, board networks can affect the governance role of independent directors. Defining director board networks as their connections based on direct ties they establish when serving on at least one common board, this paper explores the role of the network centrality of independent directors in restraining tunneling behavior by controlling shareholders in the Chinese capital market. Our empirical evidence shows that tunneling behavior by controlling shareholders is negatively related to the network centrality of independent directors and that this relationship is stronger when non-operating fund occupation is used as the measure of tunneling. The results of our study show that board networks can help independent directors to restrain tunneling behavior by large shareholders, which plays a positive role in corporate governance.
Keywords: G30; L14; M00; 650; Network; Independent director; Tunneling; Social network analysis